Critical thinking in geology and archaeology: interpreting scanning electron microscope images of a lithic tool - Nicolaysen, Kirsten P.; Ritterbush, Lauren W. (My University, 2005)
As co-instructors of an undergraduate course in Archaeological Geology, we have developed an in-class research project using the Scanning Electron Microscope (SEM) to analyze and interpret physical traces of stages in the history of a unique lithic artifact. This exercise requires preliminary instruction on percussion and pressure flaking, geological materials suited for chipped stone tool manufacture, contextual archaeological analysis, theory of electron microscope use, and post-depositional surface processes, particularly those creating natural wear due to wind or water abrasion. With this background, students acquired four images of surface and edge locations of the study artifact using the SEM. We asked students to write a description of the analytical technique, a compilation of their observations and analytical data, and an interpretation of the artifact's history. Although most students recognized that the artifact recorded multiple stages of manufacture and use, additional comparative images of water- or wind-worn, chipped or ground cherts would give students greater ability to distinguish cultural modifications from those created by post-depositional geologic processes. Students expressed enthusiasm about the project and indicated a high level of engagement on evaluations (mean score=4.3-4.4, median score=4.5-5.0 on a scale of 1 [low] to 5 [high]).
Keywords: Scanning electron microscope; Archaeology; Geology; Lithic tools; Critical thinking; Science education